Hambatan dan Strategi Pengembangan Sumber Daya Pendidik - Walewangko, Gloria Ester Verelin; Sumual, Tinneke Evie Meggy; Usoh, Elni J (JURNAL PENA EDUKASI, 2022)
Abstract: Quality education is inseparable from the teaching resources that are the driving force of education. Indonesia is faced with the problem of the low quality of educators in the background with a very complex problem. Thus the author carries out this research aims to find out what the obstacles are in developing educator resources and what steps can be a way out to continue developing educator resources. This research obtained data and information through the literature review research method in which Google Scholar indexes scientific articles. The results obtained include obstacles in developing educator resources related to competence as an educator and educator welfare. Through these obstacles, the steps that can be a strategy for developing educator resources are professional development and competence through training institutions and universities. Programs such as professional education for teachers, workshops, seminars, and teachers' working group are strategies to improve educators' competencies. Improving the compensation system also encourages the development of educator resources so that educators are expected to provide the best educational services.Keywords: barriers; development; educator resourcesAbstrak: Pendidikan yang berkualitas tidak terlepas dari sumber daya pendidik yang menjadi motor penggerak pendidikan. Indonesia di perhadapkan dengan persoalan rendahnya kualitas pendidik di latar belakangi dengan persoalan yang sangat kompleks. Dengan demikian penulis melaksanakan penelitian ini bertujuan untuk mengetahui apa saja hambatan dalam proses pengembangan sumber daya pendidik dan apa saja langkah yang sekiranya dapat menjadi jalan keluar untuk dapat terus mengembangkan sumber daya pendidik. Penelitian ini memperoleh data dan informasi di dapat melalui metode penelitian tinjauan pustaka yang di dalamnya adalah artikel ilmiah yang terindex Google Scholar. Hasil yang didapat diantaranya hambatan-hambatan dalam proses pengembangan sumber daya pendidik adalah berkaitan dengan kompetensi sebagai pendidik dan kesejahtraan pendidik. Melalui hambatan ini langkah yang bisa menjadi strategi untuk pengembangan sumber daya pendidik adalah dengan pengembangan profesionalitas dan kompetensi melalui lembaga pelatihan dan perguruan tinggi. Program-program seperti PPG, workshop, seminar, KKG menjadi strategi untuk meningkatkan kompetensi pendidik. Memperbaiki sistem pemberian kompensasi juga mendorong pengembangan sumber daya pendidik sehingga pendidik diharapkan mampu memberikan layanan pendidikan yang terbaik.Kata kunci: hambatan; pengembangan; sumber daya pendidik